Effect of upper extremity plyometric training on strength and accuracy in archery players - Dhawale, T.; Yeole, U.; Jedhe, V. (Journal of Medical Science and Clinical Research, 2018)
Plyometric training improves the strength and power of upper extremity a pre-requisite for archers. The study aimed on the effect of Upper Extremity plyometrics on strength and accuracy in archers. Materials & Methodology: Using simple random method, 60 archers between 18-30 years of both genders were selected and divided into experimental and control group.15 subjects in each group. Pre and post intervention of accuracy on score board, endurance using closed kinetic chain Upper Extremity stability test and 1RM for strength were compared. Intervention is based on plyometric training of primary archery muscles of shoulders and upper back for 3 days a week till 6 weeks. Results: After comparing pre and post intervention data using paired t test, significant improvement in accuracy (p<0.0001), endurance (p<0.0001), 1RM Right (p< 0.0001) and 1RM Left (p=0.0001) in archers were found. Conclusion: There is significant effect of upper extremity plyometrics training on Upper Extremity strength and accuracy in archers.